1994
DOI: 10.1111/j.1365-2184.1994.tb01470.x
|View full text |Cite
|
Sign up to set email alerts
|

Negative control of cell proliferation in eukaryotes

Abstract: The nucleoside diphosphate kinase (NDPK/nm23) iso-forms H1 and H2 were localized in hematopoietic tissues. Flow cytometric analysis and enzymatic assays were used to quantify the intracellular and extracellu-lar concentrations of NDPK. Bone marrow CD34 progenitors contained the highest intracellular levels of both nm23-H1 and nm23-H2. Lower levels were measured in more mature bone marrow cells, whereas peripheral blood leukocytes had the lowest expression of nm23. These data suggest a function of NDPK in early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1995
1995
2003
2003

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 163 publications
0
4
0
Order By: Relevance
“…Most of the known cell growth inhibitors are either proteins with M r of 10–40 × 10 3 or oligopeptides with M r of several hundreds (Epifanova and Brooks, 1994). In contrast, the cell growth inhibitor in the present study is unlikely to be a peptide as is suggested by its resistance to proteases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the known cell growth inhibitors are either proteins with M r of 10–40 × 10 3 or oligopeptides with M r of several hundreds (Epifanova and Brooks, 1994). In contrast, the cell growth inhibitor in the present study is unlikely to be a peptide as is suggested by its resistance to proteases.…”
Section: Discussionmentioning
confidence: 99%
“…Cell proliferation in eukaryotes is controlled by the interplay between growth inhibitors and growth stimulators, which switch the cells from growth to rest and vice versa (Epifanova and Brooks, 1994). Although growth inhibitors are biologically as fundamental as the stimulators, their structure and function are far less well characterized than those of growth stimulators.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Ample evidence shows that, the opioid peptides are inhibitors of DNA synthesis and cell proliferation in the CNS (Vértes et al . 1982; Zagon & McLaughlin 1991; Epifanova & Brooks 1994; Zagon et al . 2002) and in several peripheral tissues and cells (Maneckjee et al .…”
Section: Introductionmentioning
confidence: 99%